2013
DOI: 10.2169/internalmedicine.52.9442
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Response to Pramipexole in a Patient with Multiple System Atrophy with Predominant Parkinsonism: Positron Emission Tomography and Pharmacokinetic Assessments

Abstract: Multiple system atrophy with predominant parkinsonism (MSA-P) usually shows poor responsiveness to dopaminergic medications. We herein describe a patient with MSA-P who exhibited a good response to pramipexole but not to an ordinary dose of L-dopa. Positron emission tomography (PET) displayed severely impaired presynaptic dopaminergic availability and relatively preserved postsynaptic D2 receptor binding capacity. The pharmacokinetic analyses demonstrated relatively low bioavailability for L-dopa and adequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Parkinsonism-predominant multiple system atrophy (MSA-P), a subtype of multiple system atrophy, is a sporadic neurodegenerative disorder with symptoms that are characteristic of parkinsonism, cerebellar ataxia, and autonomic dysfunction, etc. It is important to emphasize the need for precise diagnostic differentiation between MSA-P and Parkinson's disease (PD), because they differ in prognosis and treatment response and some new surgical and pharmacologic therapies may work only in patients with PD (1).…”
Section: Introductionmentioning
confidence: 99%
“…Parkinsonism-predominant multiple system atrophy (MSA-P), a subtype of multiple system atrophy, is a sporadic neurodegenerative disorder with symptoms that are characteristic of parkinsonism, cerebellar ataxia, and autonomic dysfunction, etc. It is important to emphasize the need for precise diagnostic differentiation between MSA-P and Parkinson's disease (PD), because they differ in prognosis and treatment response and some new surgical and pharmacologic therapies may work only in patients with PD (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, only 6 out of 7 participants completed this study, and its protocol did not include placebo-controlled group. Another clinical trial showed improvement after pramipexol administration among MSA patients with no response to levodopa; however, this is only a single report (Ueda et al, 2013). In a study evaluating the effectiveness of amantadine (100 mg twice daily) in PSP and MSA, 42.9% of the PSP patients and 61.5% of the MSA patients showed partial improvement (Rajrut et al, 1997).…”
Section: Introductionmentioning
confidence: 95%